Konstruksi Komunikasi Pemulung Sampah Jakarta (Studi Fenomenologi Komunitas Pemulung Jakarta Selatan) - Miftachul Ulum (MediaKom : Jurnal Ilmiah Komunikasi, 2019)
This study describes the phenomenon of communication construction scavengers as a social problem and how the concept of self-scavengers that makes a person become scavengers and how they survive become scavengers with all the consequences of living in the city. And how the symbols that appear on the role resulting scavenger community communication patterns seen from the construction of communication scavengers. The scavengers of self-concept timbulah motive someone doing scavenged. Motive arising from scavengers generated from these scavengers before plunging into the world of scavenging and after becoming a scavenger scavenger experienced. Communication symbols exist in scavenged phenomenon in the form of verbal and non-verbal symbols. Where verbal communication is related to how the scavengers communicate orally in running their interactions. Non-verbal communication in the form of non-verbal communication in the form of accessories worn scavengers in carrying out its activities. Intersubjectivity scavengers in gathering knowledge about trashy trashy is what is most profitable for the scavengers. Keywords: Construction Of Communication, Scavengers, Phenomenon